Testicular feminization syndrome in puberty. A Case Report - Zain Alkaff, Zain Alkaff (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1999)
Background: It is important to diagnose testicular feminization due to other abnormalities with similar clinical findings which needs different treatments.Aim: To diagnose early testicular feminization syndrome by clinical findings, hormone levels, and chromosome analysis.Design: Review of reported cases.Setting: A university hospital. Patient: Phenotypic girl aged 9 years with abnormal external genitalia revealed large clitoris-like structure, normal labia majora, a blind vaginal pouch and no palpable uterus and adnexa. Results: The uterus and adnexa of the patient at ultrasonography and laparoscopy examination were proved to be absent. The serum testosterone concentration was not substantially increased and the karyotype was 46XY. Further examination found left testis in inguinal canal and the right one in labia majora. From biopsy it was found that both seminiferous tubules were in development phase mostly with spermatogonia, and several part in spermatocyte phase. The diagnosis was testicular feminization (androgen insensitivity syndrome). Conclusions: Cases of primary amenorrhea, incomplete external genitalia, and vagina agenesis/hypogenesis, are important to be early diagnosed by investigating the sex chromosome, gonads, sex hormone, genitalia, and sex psychology. Because of the increased risk of malignancy, an orchidectomy has to be performed.Key words : testicular feminization - normal male 46XY - female external genitalia - orchidectomy